The complex treatment of acute pancreatitis using miniinvasive surgical treatment - G. I. Ohrimenko; N. G. Golovko; V. A. Grushka; T. S. Gavrilenko; P. G. Kocherov (Zaporožskij Medicinskij Žurnal)
Nowadays methods used in acute pancreatitis diagnostic do not allow to find the most optimal indications, terms of surgical drainage approaches in surgical treatment of acute pancreatitis.